Barriers to Skill Acquisition: Evidence from English Training in India - Tarun Jain; Pushkar Maitra; Subha Mani (Institute for the Study of Labor (IZA), 2016)
Skill development is increasingly viewed as a way to escape the low education – high unemployment trap in developing countries. Consequently, policy makers in these countries are extensively investing in skill development programs. However, participation and completion rates in many of these programs remains low. This paper investigates factors that prevent individuals from acquiring spoken English, an important skill with potentially high returns in the labor market. Using data from a field experiment in India that subsidizes the cost of learning spoken English, we find that full subsidy (compared to partial or no subsidy) positively effects the probability of participating in a spoken English training program. Conversely, distance to the training center, pre-existing knowledge of spoken English, and past enrollment in a similar course act as significant barriers to take-up. These findings suggest that multidimensional policy solutions are required to overcome the barriers to skill development in developing countries.
Keywords: I25; J24; J44; 330; skill development; vocational training; spoken English; field experiment; India